2015
DOI: 10.3747/co.22.2585
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Mammography Debate: A Moderate Perspective

Abstract: After some decades of contention, one can almost despair and conclude that (paraphrasing) "the mammography debate you will have with you always." Against that sentiment, in this review I argue, after reflecting on some of the major themes of this long-standing debate, that we must begin to move beyond the narrow borders of claim and counterclaim to seek consensus on what the balance of methodologically sound and critically appraised evidence demonstrates, and also to find overlooked underlying convergences; af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 139 publications
0
6
0
Order By: Relevance
“…Notwithstanding, the contribution of breast self-examination, clinical breast examination, ultrasonography and even mammography to reduce the number of deaths from cancer is currently a source of controversy. [16] However in developing countries were late presentations is rampant, promoting the practice of breast self-examination, clinical breast examination and regular mammography screening remains advantageous. Mammography is gradually becoming more available in health care facilities across Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, the contribution of breast self-examination, clinical breast examination, ultrasonography and even mammography to reduce the number of deaths from cancer is currently a source of controversy. [16] However in developing countries were late presentations is rampant, promoting the practice of breast self-examination, clinical breast examination and regular mammography screening remains advantageous. Mammography is gradually becoming more available in health care facilities across Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…Like the screening debates that preceded it, the controversy surrounding overdiagnosis has now settled into a familiar pattern. It focuses on largely technical arguments over statistical assumptions, corrections for lead time bias and varied demographics 23 , 24 that create uncertainties in the data and ultimately have shifted the debate into the realm of opinion, rather than fact. Recent characterization of a molecular profile to define an ultralow risk biology may provide a tool to more objectively categorize ultralow risk breast cancers that have little systemic risk of progression.…”
Section: Introductionmentioning
confidence: 99%
“…The Independent UK Panel on Breast Cancer Screening reported that for every 10 000 UK women aged 50 years invited to screening for the next 20 years, 43 deaths from breast cancer would be prevented and 129 cases of breast cancer, invasive and non‐invasive, would be over diagnosed (Marmot, ). The purpose of this editorial is not to resolve the debate about the risk‐benefit ratio of mammography but to place this debate in the context of primary care clinical practice (Kaniklidis, ).…”
mentioning
confidence: 99%
“…The purpose of this editorial is not to resolve the debate about the risk-benefit ratio of mammography but to place this debate in the context of primary care clinical practice (Kaniklidis, 2015).…”
mentioning
confidence: 99%